Study of predominant multiple intelligences in bilingual didactic audiovisual media - Morilla García, Cristina; Espejo Mohedano, Roberto (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective of this research is the analysis of the multiple intelligences in the audiovisual content selected by a company that develops digital resources for primary education in contexts of educational bilingualism. In order to carry out this study, a set of 100 videos from the analyzed platform, containing 6000 videos, have been randomly selected. In each of the analyzed videos, it has been verified which intelligences are those multiple intelligences that most predominate in the total of the analyzed videos.